Program Kebersihan Lingkungan Kampus untuk Menciptakan Hidup Sehat dan Nyaman - Wakid Evendi; Milda Azzania; Rommy Hardyansah; Muhammad Yusron Maulana El-Yunusi; Didit Darmawan (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2026)
The environmental cleanliness program around the campus is an important effort to maintain the comfort and beauty of the environment for the entire local community. This activity aims to encourage the community to work together in cleaning the surrounding environment. The program is carried out using the Participatory Action Research (PAR) approach, a collaborative model that places the community as active participants in every stage of the activity, starting from identifying problems, designing plans, implementing programs, to conducting evaluations. The cleanliness program carried out in success serves as concrete evidence that collaboration between the community and various campus stakeholders can produce significant outcomes in maintaining environmental cleanliness and comfort. The existence of this environmental cleanliness initiative has also increased public awareness and concern for protecting their environment. Furthermore, the program contributes to creating a healthy and comfortable environment for all local residents. The desired positive changes can be achieved as expected, and the spirit of cooperation will continue to grow and become a habit that brings long-term benefits for the health and comfort of the surrounding community.